Strengthening the Reading Comprehension of Students Using a Context Clue - Oclarit, Rhoderick P; Casinillo, Leomarich F (LPPM Undiksha, 2021)
One of the most important aims in education is the students’ reading comprehension to be developed. Seemingly, the goal of the curriculum emphasis on students’ constructing knowledge, higher order thinking skills and information processing skills. Hence, to improve the learners’ academic achievement, students should be exposed to a particular form of teaching strategy or intervention. A reading comprehension of a student is the understanding of what is read. The intent of this study is to determine the impact of context clue as intervention for reading comprehension. The study was conducted in 8 elementary schools where the respondents are bona fide Grade 4 learners. The study investigated the effectiveness of context clues as aid for reading comprehension through enhancing student’s vocabulary which utilizes the revised Philippine Informal Reading Inventory (Phil-IRI). Phil-IRI result of the last three years were gathered and found out to be quite low. On the other hand, result of the Phil-IRI of the current school year was also gathered and shows to have significant difference to the last three years. Moreover, the pre-test to post-test result shows to have a significant improvement to students’ reading ability. Thus, context clues have exhibit positive impact to reading comprehension of grade 4 students. It is concluded that the use of context clue increases the reading comprehension of the students. Students that are modeled context clue strategies over a period of time improve their ability to locate clues in the text and alleviate comprehension level.